Evidence for Root Kin Recognition in the Clonal Plant Species Glechoma hederacea - Goddard, Ellen L.; Varga, Sandra; John, Elizabeth A.; Soulsbury, Carl D. (Frontiers in Ecology and Evolution, 2020)
Plant competition belowground is a crucial factor that determines plant fitness and shapes plant communities. It has been shown that roots possess the ability to recognise between self and non-self individuals and modify their growth patterns accordingly. Roots may also be further able to discriminate between kin and non-kin roots. Competition is stronger with non-kin than kin neighbours, but whether root growth patterns determined by kin interactions are modified in stressful environments is largely unexplored. In this study we used two different experimental set-ups to confirm whether the clonal species Glechoma hederacea exhibits kin recognition between roots, and how water limitation modifies this response. A split-root design was conducted using a focal clonal fragment of G. hederacea placed onto the ridge that separated two adjacent containers: either square petri-dishes boxes with 200 ml of soil or 400 ml clear pots. Focal plants were randomly allocated to either growing alone or in competition with another G. hederacea ramet (of similar size taken from the same stolon as the focal plant) or a non-kin individual (a ramet selected from a different population). A water limitation treatment was applied to both experiments. Five root parameters were measured during the experiment using boxes: the maximum depth and the maximum width of the deepest root, the depth and the maximum width of the widest root, and the total number of roots visible. All plants were harvested after 36 days and several final root measurements were taken and analysed using GiaRoots. Our results show that G. hederacea roots have kin recognition mechanisms, showing a significant tendency to avoid growing towards a non-kin neighbour but not avoiding the roots of a kin plant, even though the presence of a kin plant modifies root distribution within the soil. As expected, water limitation significantly affected plant growth and root parameters, but this effect was not related to neighbour kin identity. Taken together, our results confirm the existence of root recognition in this species and suggest that the mechanisms of kin recognition are probably related to a root-derived chemical cues, as recognition took place before physical contact occurred.